Digital workflow to fabricate a 3D-printed monobloc mandibular advancement appliance for primary snoring and obstructive sleep apnoea - Lau May Nak; Ong Kah Shin; Chong Cheng Lin; Pang Priyantha Lee Yek (Australasian Orthodontic Journal, 2025)
Mandibular advancement appliances (MAAs) are used to treat primary snoring and obstructive sleep apnoea (OSA) by advancing the mandible to maintain upper airway patency during sleep. The conventional fabrication of custom-made MAAs requires skilled technicians and specialised laboratories, resulting in longer processing times and higher outsourcing costs. Advancements in 3D-printing technology offer an efficient in-office alternative. The present paper aims to demonstrate the potential of digital technology in fabricating in-office, 3D-printed, non-adjustable monobloc MAAs.